Seleção e caracterização de peptídeos recombinantes miméticos de antígenos do vírus da dengue por "PHAGE DISPLAY" - Santos, Paula de Souza (2006)
Dengue fever is caused by an arbovirus of the Flaviridae family, transmitted from person to another through an intermediate fly vector, Aedes aegypti. It is a tropical and subtropical infectious disease characterized by fever and strong pain in joints, which could also lead to bleeding in its hemorrhagic form. In this investigation, Phage Display technology was used to identify recombinant peptides with affinity to polyclonal antibodies (IgY) raised in immunized chickens with total proteins of the DENV-3 culture. Animal sera was purified in a HiTrap column and concentrated through dialysis. The IgY s were immunoreactive against DENV cultures, but were not type specific. Phage clones were selected from a random peptide library (PhD-7) in four cycles of biopanning against IgY. Selected phages were amplified in deepwell microtiter plates and submitted to ELISA tests. Immunoreactive clones against IgY were sequenced, translated and analysed through bioinformatics. Fourteen distinct clones were selected and aligned against viral proteome sequences and among themselves. Three consensus sequences among phage clones were detected: VLRN, APP and LPP. The peptide search in BLASTp showed similarity to the following viral proteins: polyprotein, envelop, and the nonstructural proteins NS1, NS2a, NS3 and NS5. All of them have matched with DENV-1, -2, -3, and/or -4 sequences, corroborating with the lack of type specificity of the raised IgY. Considering the VLRN motif, the analyses of antigenicity indexes of similar peptides demonstrated that its antigenicity is highly influenced by neighboring residues. Three-dimensional analysis of the DENV-2 capsid protein, with the alignment of the VLRN motif, have identified two target sequences, NRVSTVQQL and EIGRMLNILNRR, that are present in the polyprotein of all four viral types, which may contain the two possible domains VxRN and LRN, respectively. Six selected phages have presented known protein domains, and five of them presented specific phosphorylation and glycosylation sites, similar to known eukaryotic viruses; however, they may not be physiologically active sites in the dengue virus. Finally, the peptides were used to detect human IgG and IgM. ELISA tests were performed in two patients with isolated infections of DENV-1 or DENV-3. The reactivity of the 14 clones was superior to total antigens obtained from cultures, but they were not type specific.